How individuals perform customer knowledge absorption practices - a contextual approach to open innovation. (9th May 2019) - Mahringer, Christian A.; Rost, Martin; Renzl, Birgit
Enabling individuals to perform open innovation practices requires an in-depth analysis of the context in which those practices are enacted. However, research on the context within which open innovation is practiced, is still in its beginning. This paper develops a theoretical framework of the relationship between open innovation practices, individuals performing those practices, and context factors that enable or constrain those individuals carrying out open innovation practices. Moreover, the paper reports empirical research on context factors enabling or constraining salespeople in performing customer knowledge absorption practices, a specific subset of open innovation practices, in a pharmaceutical packaging machines firm. The paper contributes to open innovation research by: 1) advancing a contextual view on open innovation; 2) emphasising the need to distinguish between open innovation practices that provide an analytical tool to unravel the social dimension of open innovation; 3) identifying context factors that enable or constrain customer knowledge absorption.